Epidemiolog Study and Identification for Intestinal Parasites have Influence on Passer domesticus in Tikrit City, Iraq - Abid A. Jenzeel; Wisam H. Abd AL-Hade; Abdullah H. Abdullah (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
During the period from September 2013 till the end of July 2014 ,a total of 340 birds Passer domesticus were collected from Tikrit city . The study revealed the infection of birds with seven species of  cestoda  helminthes , belonging to the genus Raillietin . These species included  R. tetragona , R. echinobothrida , R. cesticellus and R. ransomi with prevalence infection of 36.1% , 30.1% . 15.0 % and 1.8 % respectively . And the genus Choanotaenia . These species included  C. infundibulum and C. passerine with pervatence infection of 15.0% and 0.6% respectively . And the genus Anonchotuenia . The species included  A.globate with prevantence infection 1.2% .                                                                                Among of these parasites R. ransomi , C. passerine and  A. globate were reported  here for the first time in Iraq , in addition , P. domesticus  is considered as a new host in Iraq for R. tetragona , R. echinobothrida , R. cesticellus and C. infundibulum .